Altered states of consciousness and ritual in late Bronze Age Cyprus - Collard, David (2011)
This thesis combines an anthropological approach to the study of Altered States of Consciousness (ASCs) with a detailed analysis of previously published evidence for the consumption of psychoactives from Late Bronze Age Cypriote (Late Cypriote) contexts to investigate the possibility that such mental phenomena may have been utilised within religious rituals of this period. This evidence primarily consists of ceramic vessels associated with the consumption of opium and alcohol (often supported by organic residue analysis), but also includes iconography, ethnographic and historical sources and neuro-psychological studies of the effects of the relevant psychoactive substances. This range of evidence is analysed using a ‘contextual analysis’ designed to interpret the meanings (symbolic and socio-political) associated with the ASCs these substances can induce, particularly in relation to ritual practice.